The Importance of the Family In Raising the Physical Culture of Youth - Shonazarov O‘tkir (International Journal on Integrated Education, 2023)
This article is devoted to issues such as the importance of the family in improving the physical culture of young people, the organization of an educational process to successfully solve the problems of physical education of young people in the family, and the rise of young people as a healthy generation. Key words: Family, youth, healthy generation, healthy lifestyle, sport, physical education, physical culture.